Initiating The Concept of Sui Generis of the Legal Protection of Communal Intellectual Property in The Philosophy of Science Perspective - Taufik H. Simatupang (Jurnal Penelitian Hukum De Jure, 2022)
This study aims to answer how the protection of Communal Intellectual Property rights in Indonesia and how the concept of sui generis can be applied from the perspective of the philosophy of science. The research method used is a doctrinal legal research method with an approach to legislation, legal concepts, and theories through literature search. The results show that until now Indonesia has recorded and documented the Communal Intellectual Property, both by the Directorate General of Intellectual Property of the Ministry of Law and Human Rights and the Directorate General of Culture of the Ministry of Education and Culture. Including the recording and registration of Intangible Cultural Heritage to UNESCO. However, legal protection of Communal Intellectual Property cannot be carried out optimally considering that several laws and regulations governing Communal Intellectual Property, especially those related to Traditional Cultural Expressions, are not in harmony with one another, besides thatno law specifically regulates this Communal Intellectual Property. On the other hand, considering the problems that are not easy to regulate, considering intellectual property protection which is individual protection while Intellectual Property Rights arecommunal. Therefore, Indonesia needs to immediately regulate the protection of Communal Intellectual Property in the form of law through the idea of the sui generis concept.